Association of vitamin K with cognitive decline and neuropathology in community‐dwelling older persons. Issue 1 (20th April 2022) - Booth, Sarah L.; Shea, M. Kyla; Barger, Kathryn; Leurgans, Sue E.; James, Bryan D.; Holland, Thomas M.; Agarwal, Puja; Fu, Xueyan; Wang, Jifan; Matuszek, Gregory; Schneider, Julie A.
Abstract: Higher vitamin K intakes have been associated with better cognitive function, suggestive of a vitamin K mechanistic effect or simply reflective of a healthy diet. To test the hypothesis that brain vitamin K is linked to cognitive decline and dementia, vitamin K concentrations were measured in four brain regions, and their associations with cognitive and neuropathological outcomes were estimated in 325 decedents of the Rush Memory and Aging Project. Menaquinone‐4 (MK4) was the main vitamin K form in the brain regions evaluated. Higher brain MK4 concentrations were associated with a 17% to 20% lower odds of dementia or mild cognitive impairment (MCI) ( P ‐value < .014), with a 14% to 16% lower odds of Braak stage ≥IV ( P ‐value < 0.045), with lower Alzheimer's disease global pathology scores and fewer neuronal neurofibrillary tangles ( P ‐value < 0.012). These findings provide new and compelling evidence implicating vitamin K in neuropathology underlying cognitive decline and dementia.